The Effect of Dividend Policy, Capital Structure, and Exchange Rate on Stock Returns in Industrial Sector Business Entities - Maulana, Arif; Hendarin, Rega Mawarni Nur; Haris, Abdul (Devotion : Journal of Research and Community Service, 2024)
The purpose of this study is to examine how Dividend Income, Capital Structure, and Exchange Rate affect Stock Market Performance. The sample consisted of 12 companies trading on the Indonesia Stock Exchange (IDX) selected using the Purposive Sampling method, resulting in 63 observations for each variable.  Data from audited financial statements, tax reports, and stock market prices are published by Bursa Indonesia (IDX).  Data analysis was performed using regression analysis techniques.  The results of this study show that the Exchange Rate, Dividend Payout Ratio (DPR), and Debt to Equity ratio (DER) all have a significant impact on stock prices.  Individually, the Exchange Rate and DER have significant effects, with the Exchange Rate having a negative effect and DER having a positive effect, but the DPR having no significant effect.  The coefficient of determination shows that 10.8% of the stock price variation can be explained by the three variables studied, while 89.2% can be explained by other factors not included in the study.